Crowdsourcing for language learning and linguistic resource creation - Lionel Nicolas; Verena Lyding (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave, 2022)
The current special issue of the journal Slovenščina 2.0 focuses on the newly explored combination of crowdsourcing, language learning and linguistic resource creation. It contains five articles and one project report, providing insightful discussions on several aspects of this combination, as well as results which help us understand its versatile potential and the challenges to address in order to better exploit it.